Should enteroviruses be monitored in natural recreational waters - Šarmírová, Soňa; Nagyová, Viera; Štípalová, Darina; Drastichová, Iveta; Šimonyiová, Danka; Sirotná, Zuzana; Kissová, Renáta; Pastuchová, Katarína; Tirpáková, Jana; Kuba, Daniel; Klement, Cyril; Bopegamage, Shubhada (Central European Journal of Public Health, 2016)
Enteroviruses (EVs) infections occur worldwide. Although, infections by these viruses are often asymptomatic and go unnoticed, they can be shed in stool for several weeks. The EVs re associated with sporadic outbreaks and a wide range of clinical symptoms, occasionally accompanied with fatal consequences. Presently in the Slovak Republic (SR) recreational waters are tested only for bacterial indicators. Our aim was to monitor EVs in recreational waters. Water samples were collected during the years 2012-2014 from different recreational natural lakes in Central and West regions of SR. The samples were concentrated by centrifugation using the two-phase separation method recommended by the World Health Organization (WHO) used for EVs surveillance in the treated sewage waste water. Each of the two phases collected from the samples was analysed by polymerase chain reaction for detection of EVs and primary sequencing was done. Our study demonstrated presence of EVs in three localities consecutively for three years, indicating a probability of constant local source of faecal contamination. This is the first monitoring report on the occurrence of EVs in the natural recreational waters in SR.
Keywords: Feces; mikrobiologie vody; Slovakia; Water Microbiology; rekreace; lidé; Environmental Monitoring; polymerázová řetězová reakce; Enterovirus; Humans; Polymerase Chain Reaction; Slovenská republika; sladká voda; Recreation; Fresh Water; monitorování životního prostředí; feces